Sustainable Human Resource Management, Unions and Equality-Enabling Practices: A Framework-Based Systematic Literature Review and Directions for Future Research - Muduli, Ashutosh; Bharath, Sindu (Relations industrielles / Industrial Relations, 2024)
In response to Sustainable Development Goals 5 and 10 (SDGs), organizations are collaborating with unions to integrate sustainability into their strategies by adopting socially responsible HR practices for social equity and equality. In this study, grounded in social justice ideology, we explore the antecedents, decisions and outcomes of sustainable HRM practices that promote workplace equity and equality with union support. We used a framework-based systematic literature review (SLR) method, guided by the antecedents-decisions-outcomes (ADO) framework of Paul et al. (2023), and followed Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) protocols to ensure comprehensive and transparent reporting. Using the ADO framework, we identified organizational culture and values, stakeholder engagement, union trends, legal framework and regulations, collective agreements and company size as “antecedents.” “Decisions” encompassed inclusive recruitment and hiring practices, equal pay and compensation initiatives, diversity and inclusion training, flexible work arrangements and mechanisms for conflict resolution and grievance handling. “Outcomes” included improved employee well-being, enhanced productivity and performance, greater support for diversity and inclusion and a positive impact on employee health and safety. Each of the explored practices corresponded to one of three types of social justice. We suggest several avenues for future research by identifying critical gaps in theory and practice.